부산도시철도 1호선의 라돈농도 분포 및 특성에 관한 연구 - 최성우(Seongwoo Choi); 차영욱(Youngwook Cha); 조영만(Youngman Cho); 조정구(Jeonggu Cho) (Daehan hwan'gyeong gonghag hoeji, 2020)
목적:실내 라돈은 제한된 공간에서 인체 건강에 심각한 악영향을 미친다. 도시철도 역사 대부분은 지하공간에 위치하고, 지하철과 같은 지하공간은 라돈성분이 증가하는 것으로 알려져 있다. 방법:RAD-7을 이용하여 지하철 1호선에서 실내공기의 라돈농도를 연속측정하였다. 결과 및 토의:측정 결과 40개 지하철역에 측정한 평균 라돈농도는 8.9 Bq/m3이었으며, 심도가 깊은 지하역사에서 상대적으로 높은 라돈농도가 측정되었다. 지하철 운행이 중단되고 환기시설이 가동되지 않는 0시에서 5시에 라돈농도가 증가하였고, 승강장과 대합실에서 측정한 평균 라돈농도는 온도가 낮을수록 높은 것으로 나타났다. 결론:부산 지하철 1호선은 비화강암 지역에 위치하여 상대적으로 낮은 라돈농도가 나타났다. Objective:Adverse health effects of Radon with a particular focus on indoor environment has been outlined. Most of the metro stations and platforms are situated under the ground where relatively enhanced concentration of radon has been observed. Method:On-line measurements of indoor Radon have been made in Metro Line 1 in Busan using RAD-7. Results and Discussion:The average concentration of Radon was 8.9 Bq/m3 (n=40). In general, a positive relation was shown between the level of radon and the depth of station. Slightly enhanced radon concentrations were observed between 0 a.m. ~ 5 a.m. when the station is closed under the non-operation of ventilation system. Interestingly, the negative relation was seen between the radon revel and temperature. Conclusions:Relatively low levels of indoor radon has been observed in Metro Line 1 in Busan, which may be associated with geographical location of non-granite regions. KCI Citation Count: 5